KARAKTERISTIK PENDERITA OSTEOARTRITIS RAWAT JALAN DI RSUD DR. PIRNGADI MEDAN TAHUN 2015 - Riska Juliana M; Rahayu Lubis; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Osteoarthritis (OA) is a disease caused by the wear of joints, demage of cartilage in the outer layers caused by repeated used of joints can lead to disability. According to WHO, 8,1% of total population in Indonesia suffering from OA. This study aims to research the characteristics of OA patients in outpatient in RSUD Dr. Pirngadi Medan in 2015, descriptive case series design. Data were analyzed by chi-square test, Fisher, and Kolomogorov-Smirnov. The population was 967 OA patient in outpatient and the sample was 96 patient. The research showed that the highest proportion of OA patients at age group 45 - 59 (39,6%), female (80.2%), Muslim (54.2%), senior secondary education (69.8%), from the city of Medan (74%), the location of the genus joint (53.1%), the largest other disease is hypertension (29.2%), with pharmacological (91.7%), OA patient the number of visit was ≤ 3 times (63,5%) and cost source from JKN (87.5%). There was no significant difference between age and the joint location. There was no significant difference between the gender and the joint location and there was no significant difference occupation and the joint location. To the risk population of OA in order to carry out examination of the bones to prevent damage to bones or joints are more severe. Patient with OA, particulary 45-65 years old and have obesity should not do more activity, especially in the genus joint and is recommended for reducing weight through proper diet. Patient with OA should receive treatment of physiotherapy rather than taking non-steroidal anti-inflammatory drug to prevent an increase in hypertension. To RSUD Dr. Pirngadi Medan, field the complements medical record OA patients by add BMI patients and history of injury patient. Key words: OA, Patient Characteristic